Surgery for acute infective endocarditis: epidemiological data from a Spanish nationwide hospital-based registry. (12th April 2018) - Bustamante-Munguira, Juan; Mestres, Carlos-A; Alvarez, Pablo; Figuerola-Tejerina, Angels; Eiros Bachiller, Rocio; Gómez-Sánchez, Esther; Alvarez, Francisco Javier; Resino, Salvador; Castrodeza, Javier; Tamayo, Eduardo
Abstract: OBJECTIVES: Infective endocarditis (IE) is a serious and eventually lethal disease with rising incidence in the past couple of decades. The aim of this study was to evaluate the contemporary epidemiological trends of surgical endocarditis patients, to analyse the clinical outcomes and to study their profile, associated prognostic factors and costs. METHODS: This is a retrospective study of all patients admitted for IE in Spanish hospitals and discharged between 1 January 1997 and 31 December 2014. Data were extracted from the minimum basic data set of the National Surveillance System for Hospital Data in Spain provided by the Spanish Ministry of Health. Hospitalizations, comorbidities, outcomes and costs were analysed. RESULTS: In total, 34 399 patients with IE were included; 15.7% of patients received surgical treatment and 84.3% received medical treatment only. Surgical patients were mostly men (71.9%) and had a lower mean age (59.2 ± 16.08 years) than the medical treatment group ( P  < 0.0001). Mortality among surgical patients showed a decreasing trend between 1997 (32.0%) and 2014 (22.7%) and increased with age (47.6% in ≥85 years of age). Length of hospital stay and the percentage of patients with organ dysfunction were also higher in this group. The cost of the surgical treatment group was higher and increased since 1997 (15 259.22 euros), remaining stable from 2010 (40 700 euros) ( P  < 0.0001). CONCLUSIONS: Surgical treatment in IE has trended upwards in Spain during the last 2 decades. Patients are getting older and more frequently experience organ dysfunction. Mortality ratio steadily declined without changes in the length of hospital stay.